Securing our Future - Dockery, Alfred Michael; Duncan, Alan; Nguyen, Ha; Ong, Rachel (Curtin University, Bankwest Curtin Economics Centre, 2015)
Securing our Future is the sixth report in the Bankwest Curtin Economics Centre’s Focus on Western Australia series. It brings new evidence to an important policy issue with a focus on the West Australian context. After presenting some key trends on demographic changes and projections in Western Australia compared to the rest of Australia, this report explores a range of issues that are pertinent to older West Australians. These include their economic and social participation, health, wellbeing and quality of life, housing and care needs, and financial security in later life.